2014
DOI: 10.3389/fmicb.2014.00061
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation couples Chloroflexi and sulfate-reducing bacteria to Cyanobacteria in hypersaline microbial mats

Abstract: Past studies of hydrogen cycling in hypersaline microbial mats have shown an active nighttime cycle, with production largely from Cyanobacteria and consumption from sulfate-reducing bacteria (SRB). However, the mechanisms and magnitude of hydrogen cycling have not been extensively studied. Two mats types near Guerrero Negro, Mexico—permanently submerged Microcoleus microbial mat (GN-S), and intertidal Lyngbya microbial mat (GN-I)—were used in microcosm diel manipulation experiments with 3-(3,4-dichlorophenyl)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 63 publications
9
64
0
Order By: Relevance
“…Similarly, the photosynthetic mats in the coastal Um Alhool area (Qatar) are subject to dynamic evaporation and characterized by SRRs which correlate with the presence of diverse SRB, including Desulfovibrio, Desulfococcus and Desulfonema phylotypes (Al-Thani et al, 2014). In hypersaline microbial mats from Elkhorn Slough, California and Guerro Negro, Mexico (Lee et al, 2014), a nighttime cycling of hydrogen was recently reported, with H 2 being produced by fermenting cyanobacteria in the dark and consumed by members of the Desulfobacterales. According to single-cell analysis based on 15 N 2 -labelling, N 2 fixation in these mats is performed by the cyanobacterial members (Lyngbya phylotypes) with no apparent contribution from deltaproteobacterial SRB (Woebken et al, 2015).…”
Section: Microbial Matsmentioning
confidence: 97%
“…Similarly, the photosynthetic mats in the coastal Um Alhool area (Qatar) are subject to dynamic evaporation and characterized by SRRs which correlate with the presence of diverse SRB, including Desulfovibrio, Desulfococcus and Desulfonema phylotypes (Al-Thani et al, 2014). In hypersaline microbial mats from Elkhorn Slough, California and Guerro Negro, Mexico (Lee et al, 2014), a nighttime cycling of hydrogen was recently reported, with H 2 being produced by fermenting cyanobacteria in the dark and consumed by members of the Desulfobacterales. According to single-cell analysis based on 15 N 2 -labelling, N 2 fixation in these mats is performed by the cyanobacterial members (Lyngbya phylotypes) with no apparent contribution from deltaproteobacterial SRB (Woebken et al, 2015).…”
Section: Microbial Matsmentioning
confidence: 97%
“…Most hydrogenase transcripts were attributed to cyanobacterial [NiFe]-hydrogenases. Chloroflexi and sulfate reducing bacteria are the main consumers of the cyanobacterial fermentation products [36 ]. A study of lipids in a higher-salinity, gypsum-containing mat at Guerrero Negro provided a wealth of biomarkers witnessing the vertical stratification of different prokaryotes [37].…”
Section: Studies In Saltern Pondsmentioning
confidence: 99%
“…This also increases carbonate alkalinity favoring CaCO 3 precipitation. A recent study in hypersaline mats of Guerrero Negro, Mexico, estimated that nearly all the photosynthetically-fixed CO 2 was excreted as fermentation products during nighttime by cyanobacteria and that sulfate reducing bacteria consumed virtually all of this carbon and H 2 [60]. In microbialites, sulfate reduction has been directly correlated to CaCO 3 precipitation and the formation of micritic crusts [15,58].…”
Section: Changes In Microbial Diversity In Response To Elevated Co 2 mentioning
confidence: 99%